2019
DOI: 10.1111/gfs.12437
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous effect of selfing and Epichloë endophyte on forage, seed yield and turf characteristics of perennial ryegrass (Lolium perenne L.)

Abstract: Ryegrass (Lolium perenne L.) is a putative turf and forage plant characterized as mainly outcrossing in which the extent of self‐fertilization and its consequences has not been investigated. In this study, selfed and half‐sib family seeds were obtained from ten clonally propagated ryegrass plants among which two were endophyte‐free (EF) and eight were endophyte‐infected (EI). Then, 20 seed populations plus two commercial varieties of Speedy and Vigor were sown and evaluated in a biennial experiment for their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Our results demonstrated that the self-pollinating genotype of Lolium perenne (S10) might provide a better buffer in response to drought stress. Therefore, self-pollinating genotypes of the plant might be advantageous over cross-pollinating ones due to having more gain for desired traits, including drought stress resistance after fixation in genetic loci and selection for the well-performed characteristics [13]. In our study, it seems that the S10 genotype is a potential new genetic resource with a self-pollinating reproductive system that could be introduced to different genetic backgrounds for better resistance to biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Our results demonstrated that the self-pollinating genotype of Lolium perenne (S10) might provide a better buffer in response to drought stress. Therefore, self-pollinating genotypes of the plant might be advantageous over cross-pollinating ones due to having more gain for desired traits, including drought stress resistance after fixation in genetic loci and selection for the well-performed characteristics [13]. In our study, it seems that the S10 genotype is a potential new genetic resource with a self-pollinating reproductive system that could be introduced to different genetic backgrounds for better resistance to biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 86%
“…Lolium perenne plant material of this experiment consisted of one well-performed genotype of S10, selected from the previous experiment [13] and two commercial populations of Vigor and Speedy Green or in short Speedy from Barenbrug (Barenbrug Co., the Netherland). Thus, three genotypes in this research were examined in a pot culture in a greenhouse according to a completely randomized design with three replications.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It also reduces access to endophyte-compatible genotypes. In contrast, inbreeding may stabilize endophyte behaviour by preserving the genetic structure of the plant (Saikkonen et al 2004;Torkian et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of endophyte presence on cultivar competitiveness 17 found that endophyte carrying turf grass cultivars differed in measures of composition, structure and nutrient cycling from endophyte free cultivars. Recent work 18 concluded that endophyte infection in perennial ryegrass could significantly increase days to heading and number of seeds per head, and decrease leaf length and the number of spikes per plant. This study further indicated that there were genetic differences between the cultivars.…”
mentioning
confidence: 99%